A bio-based flame retardant composition and its use in the preparation of polylactic acid composites
By using a compound flame retardant of phosphorylated chitosan and M-EGCG in polylactic acid composites, the problems of flammability and decreased mechanical properties of polylactic acid have been solved, achieving high-efficiency flame retardancy and improved mechanical properties, making it suitable for high-end applications.
Patent Information
- Application Number
- CN202511259793.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-09-04
Smart Images

Figure CN120718351B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polylactic acid composite materials technology, and more specifically, to a bio-based flame-retardant composition and its application in the preparation of polylactic acid composite materials. Background Technology
[0002] Polylactic acid (PLA), as a biodegradable polymer material, is widely used in packaging, textiles, 3D printing, and electronic devices due to its renewable raw materials and environmentally friendly characteristics. However, PLA's high flammability and combustion dripping properties make it difficult to meet the high fire safety requirements of applications such as building interiors and electronic device housings.
[0003] A common method in the prior art to improve the flame retardant properties of PLA is to add flame retardants, such as phosphorylated chitosan (PCS). Although adding phosphorylated chitosan to PLA can improve its flame retardant properties, it can easily lead to a decrease in the mechanical properties of the material, such as a decrease in impact strength and tensile strength, which cannot meet the mechanical property requirements of polylactic acid materials.
[0004] Therefore, there is an urgent need in the field to provide a bio-based flame retardant that can not only improve the flame retardant properties of polylactic acid (PLA) but also give PLA materials good mechanical properties, so as to promote the application of PLA in a wider range of fields. Summary of the Invention
[0005] To address the aforementioned problems in the prior art, this invention provides a bio-based flame-retardant composition and its application in the preparation of polylactic acid composite materials.
[0006] In a first aspect of the invention, a bio-based flame retardant composition is provided, comprising phosphorylated chitosan and M-EGCG, wherein M is a transition metal element, and M-EGCG is a complex of epigallocatechin gallate (EGCG) and a transition metal ion; wherein the mass ratio of M-EGCG to phosphorylated chitosan is 1:1 to 5.
[0007] In some embodiments of the first aspect of the present invention, the mass ratio of M-EGCG to phosphorylated chitosan is 1:2~4.
[0008] In some embodiments of the first aspect of the present invention, M is selected from one of the following elements: Fe, Cu, Zn, Ni.
[0009] In some embodiments of the first aspect of the present invention, the viscosity of phosphorylated chitosan is greater than 400 mPa·s, and the degree of substitution of phosphate groups, Ds, is not less than 0.5.
[0010] In some embodiments of the first aspect of the present invention, the phosphorylated chitosan is formed by a phosphorylation reaction of chitosan, and the viscosity of the chitosan is in the range of 200~800 mPa.s, and the degree of deacetylation is ≥80%.
[0011] In some embodiments of the first aspect of the present invention, the M-EGCG is Fe-EGCG.
[0012] In some embodiments of the first aspect of the present invention, Fe-EGCG is a complex formed by the reaction of EGCG with a transition metal halide.
[0013] In a second aspect of the invention, the use of a bio-based flame-retardant composition according to the first aspect of the invention in the preparation of polylactic acid composite materials is provided.
[0014] In a third aspect of the invention, a method for preparing a polylactic acid composite material is provided, wherein a bio-based flame-retardant composition according to the first aspect of the invention is added to the raw materials for preparation.
[0015] In some embodiments of the third aspect of the present invention, the raw material composition of the polylactic acid composite material, calculated by mass parts, is as follows:
[0016] 100 parts of polylactic acid;
[0017] The first aspect of the present invention contains 5 to 25 parts of a bio-based flame retardant composition.
[0018] In some embodiments of the third aspect of the present invention, the content of the bio-based flame retardant composition is 10 to 20 parts.
[0019] The present invention has the following beneficial technical effects compared with the prior art:
[0020] This invention, by compounding M-EGCG with PCS to form a bio-based flame-retardant composition, uses this composition to prepare polylactic acid (PLA) composite materials. By controlling the raw material ratio, it successfully solves the problem of decreased mechanical properties in existing PLA composite materials with only PCS flame retardant. Therefore, the bio-based flame-retardant composition of this invention not only improves the flame-retardant properties of PLA composite materials but also maintains the mechanical properties of the PLA material itself. This achieves a comprehensive improvement in the flame retardancy, mechanical properties, and environmental benefits of PLA composite materials, laying a technological foundation for their green application in high-end fields such as electronic devices and new energy vehicles. Attached Figure Description
[0021] Figure 1 The results are Fourier transform infrared (FTIR) spectroscopic analysis results of EGCG used in Example 1 and Fe-EGCG prepared in Example 1.
[0022] Figure 2The results are Fourier transform infrared (FTIR) spectroscopic analysis results of chitosan (CS) used in Example 1 and phosphate chitosan (PCS) prepared in Example 1.
[0023] Figure 3 The results show the thermal stability test results of the polylactic acid composite material prepared in Example 3 and the polylactic acid material prepared in Comparative Example 1.
[0024] Figure 4 These are scanning electron microscope images of the cross-sections of polylactic acid composite material samples prepared in Example 1 and Comparative Example 2 after impact toughness testing, wherein (a) corresponds to Comparative Example 2 and (b) corresponds to Example 1. Detailed Implementation
[0025] The present invention will now be described in detail with reference to specific embodiments and exemplary models. These specific descriptions and exemplary models are for illustrative purposes only and do not constitute any limitation on the scope of protection of the present invention.
[0026] The bio-based flame retardant composition of the present invention comprises phosphorylated chitosan (PCS) and M-EGCG. M-EGCG is a complex of epigallocatechin gallate (EGCG) and a transition metal ion, wherein the transition metal ion may be selected from Fe... 3+ Cu 2+ Zn 2+ Ni 2+ In an exemplary embodiment of the present invention, the transition metal ion is Fe. 3+ M-EGCG complexes can be generated by reacting epigallocatechin gallate (EGCG) with transition metal halides, such as FeCl3, CuCl2, and ZnCl2.
[0027] In the bio-based flame retardant composition of the present invention, to ensure the content of phosphate groups as acid and gas sources, the degree of substitution of phosphoric acid groups in the PCS is not less than 0.5, for example, the degree of substitution of phosphate groups is in the range of 0.5 to 1 or 0.5 to 0.8. The viscosity of the phosphorylated chitosan PCS is preferably greater than 400 mPa·s, and the degree of deacetylation is ≥80%.
[0028] In the bio-based flame retardant composition of the present invention, the mass ratio of M-EGCG to phosphorylated chitosan is 1:1 to 5, preferably 1:2 to 4.
[0029] This invention adds a bio-based flame retardant composition formed by the compounding of phosphorylated chitosan and M-EGCG to the raw materials for preparing polylactic acid composites, thereby simultaneously improving the mechanical properties and flame retardant properties of the composites.
[0030] In the raw materials of the polylactic acid composite material of the present invention, the proportion of the bio-based flame retardant composition is 5 to 25 parts, preferably 10 to 20 parts, based on 100 parts by weight of polylactic acid.
[0031] To promote uniform dispersion of the bio-based flame retardant composition in a polylactic acid matrix, 0.5-3 parts by weight of diffusion oil (relative to 100 parts by weight of polylactic acid) may be added to the raw materials. In a specific embodiment of the invention, 1 part by weight of methyl silicone oil diffusion oil was added.
[0032] The polylactic acid composite material of the present invention can be prepared by injection molding, and the preparation method includes the following steps:
[0033] 1. Preparation of bio-based flame retardant compositions:
[0034] Step 1.1: Preparation of M-EGCG, a complex of EGCG and transition metal ions.
[0035] M-EGCG complexes are formed by the reaction of EGCG with transition metal halides. Specifically, epigallocatechin gallate (EGCG) is dissolved in deionized water, and a certain amount of metal halide solution (such as FeCl3, CuCl2, ZnCl2, etc.) is added. The concentration of EGCG solution is 0.01~0.001 mol / L, the concentration of metal halide is 0.01~0.001 mol / L, and the molar ratio of metal ions to EGCG is 5:1~1:1. The mixed solution is reacted at 30~40℃ for 2~6 hours. The precipitate is collected by centrifugation, washed with ethanol, and dried under vacuum to obtain the EGCG-metal ion complex (M-EGCG).
[0036] Step 1.2: Preparation of PCS
[0037] Phospho-chitosan PCS can be obtained directly from existing technologies, for example, by preparing it according to existing techniques through a phosphorylation reaction of chitosan and a phosphorylating agent. The phosphorylating agent can be any known phosphorylating agent in the art; in an exemplary embodiment of this invention, P2O5 is used as the phosphorylating agent. The degree of substitution of the phosphate groups in the PCS can be controlled by adjusting the phosphorylation reaction in a manner known in the art, for example, by controlling the ratio of chitosan to the phosphorylating agent. The viscosity of the phosphate-chitosan can be controlled by adjusting the chitosan used as a raw material in the phosphorylation reaction.
[0038] Step 1.3: Preparation of bio-based flame retardant composition
[0039] M-EGCG and PCS are blended at a mass ratio of 1:1 to 5 to form a bio-based flame retardant composition.
[0040] 2. Bio-based flame-retardant compositions are used to prepare polylactic acid composites:
[0041] Step 2.1: Raw material preparation and mixing
[0042] Polylactic acid and a bio-based flame retardant composition are blended in the following proportions by weight to form a polylactic acid mixture:
[0043] 100 parts of polylactic acid;
[0044] 5-25 parts of bio-based flame retardant composition.
[0045] Step 2.2: Melt blending extrusion, pelletizing and injection molding
[0046] The polylactic acid mixture obtained in step 2.1 is melt-blended and then extruded through a twin-screw extruder. The feed zone temperature is set to 130~160℃, the heating zone temperature to 140~180℃, the melting zone temperature to 150~200℃, the die zone temperature to 150~200℃, and the rotation speed to 30~70 r / min to ensure that the material is fully melted and mixed evenly. Then, the extruded material is fed into a pelletizer through a cooling device to form polylactic acid mixture granules.
[0047] The obtained polylactic acid composite material particles are fed into an injection molding machine for injection molding to obtain polylactic acid composite material products. The temperature of the injection zone is set to 175~205℃, and the temperature of the mold zone is set to 20~40℃ to meet the requirements of polylactic acid composite material annealing treatment. The injection pressure is set to about 0.5~0.8Mpa.
[0048] The injection molding process of this invention can also employ injection molding processes for polylactic acid materials known in the art. Those skilled in the art, understanding the raw material proportions, can determine the specific injection molding process.
[0049] The viscosity values described in this invention are all viscosity values at 25°C.
[0050] The present invention will be further described in detail below through exemplary embodiments and comparative examples.
[0051] Example 1
[0052] The preparation of the bio-based flame retardant composition in this embodiment includes the following steps:
[0053] Step 1.1: Preparation of EGCG and Fe 3+ Fe-EGCG, an ionic complex
[0054] Epigallocatechin gallate (EGCG) was dissolved in deionized water to form a 0.004 mol / L EGCG solution, and a 0.002 mol / L FeCl3 solution was added. The FeCl3 solution contained Fe... 3+ The molar ratio of EGCG to Fe was 2:1. The mixed solution was reacted at 40°C for 6 hours. After the reaction was complete, the precipitate was collected by centrifugation at 8000 rpm for 30 minutes. The precipitate was washed with ethanol and dried under vacuum to obtain powdered EGCG and Fe. 3+ The ion complex (Fe-EGCG). Fourier transform infrared spectroscopy (FTIR) was used to analyze the raw material EGCG and the resulting complex Fe-EGCG in this example. The infrared spectra of both are shown below. Figure 1 As shown, this also shows that EGCG and Fe 3+ The ions formed a complex, Fe-EGCG.
[0055] The EGCG used in this embodiment was purchased from Shaanxi Yuzhou Biotechnology Co., Ltd., with a purity of ≥98%.
[0056] Step 1.2: Preparation of PCS
[0057] One part by mass of chitosan (viscosity 610 mPa·s, degree of deacetylation ≥80%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd., brand name C804730) was dissolved in 20 parts by mass of methanesulfonic acid. While stirring, two parts by mass of P2O5 were gradually added to form a mixed solution. The mixed solution was sealed and reacted at 15℃ for 6 h. The reaction solution was then poured into an ether solution, centrifuged, filtered, and washed repeatedly with ether, acetone, and methanol. After vacuum drying, phosphorylated chitosan (PCS) with a viscosity of 575 mPa·s was obtained.
[0058] Fourier transform infrared (FTIR) spectroscopy was used to analyze the chitosan CS and the phosphorylated chitosan PCS used in this embodiment. The infrared spectra of the two are shown below. Figure 2 As shown, from Figure 2 It can be seen that in PCS at 1205cm -1 Nearby and 1050cm -1 New absorption peaks appeared nearby, corresponding to the P=O bond stretching vibration peak and the PO bond stretching vibration peak, respectively, indicating that chitosan CS was successfully phosphorylated. Titration analysis of PCS revealed a phosphate group substitution degree of 0.582.
[0059] Step 1.3: Preparation of bio-based flame retardant composition
[0060] The Fe-EGCG prepared in step 1.1 and the PCS prepared in step 1.2 were weighed at a mass ratio of 1:4 and mixed evenly to obtain a bio-based flame retardant composition.
[0061] The following describes the use of a bio-based flame-retardant composition to prepare polylactic acid composite materials. The preparation steps are as follows:
[0062] Step 2.1: Raw material preparation and mixing
[0063] The raw material ratio of the polylactic acid composite material in this embodiment, calculated by mass parts, is: 100 parts polylactic acid, 10 parts bio-based flame retardant composition, and 1 part diffusion oil (methyl silicone oil). Each component is accurately weighed according to the designed raw material ratio.
[0064] Polylactic acid and bio-based flame retardant composition were placed in an oven and dried at 50°C for 24 hours. Then, polylactic acid, bio-based flame retardant composition and diffusion oil were mixed evenly to obtain polylactic acid mixture.
[0065] Step 2.2: Melt blending, extrusion, and pelletizing
[0066] The polylactic acid mixture obtained in step 2.1 is fed into a twin-screw extruder for melt mixing and extrusion. The feed zone temperature is set to 150°C, the heating zone temperature to 170°C, the melting zone temperature to 180°C, the die zone temperature to 190°C, and the screw speed to 40 r / min to ensure that the material is fully melted and mixed evenly. Then, the extruded material is fed into a pelletizer through a cooling device to obtain polylactic acid composite material masterbatch with a particle size distribution of D90 of 3 mm.
[0067] Step 2.3: Injection Molding
[0068] Polylactic acid (PLA) composite masterbatch is melted and fed into a micro injection molding machine for injection molding according to the desired product shape. During injection molding, the injection zone temperature is 195℃, the mold zone temperature is 30℃, the injection pressure is 0.7MPa, and the holding time is 50s to ensure that the composite material is uniformly filled into the mold, thus preparing PLA composite material samples (for unnotched impact strength testing, the sample size is 80mm long, 10mm wide, and 4mm thick; for tensile strength testing, the sample size is a dumbbell-shaped sample with a total length of 170mm, a narrow middle section of 80mm long, 10mm wide, and 1mm thick, as required by the GB / T 1040 series standard; for flame retardancy testing, the sample is a rectangular strip with a length of 127mm, a width of 12.7mm, and a thickness of 3mm).
[0069] Example 2
[0070] The only difference between the bio-based flame retardant composition of Example 2 and that of Example 1 is the mass ratio of Fe-EGCG to PCS. Specifically, in Example 2, the mass ratio of Fe-EGCG to PCS is 1:3.
[0071] The preparation steps for using the bio-based flame retardant composition of Example 2 to prepare polylactic acid composite material are the same as those in Example 1. The polylactic acid composite material sample of Example 2 is obtained by injection molding.
[0072] Example 3
[0073] The only difference between the bio-based flame retardant composition of Example 3 and that of Example 1 is the mass ratio of Fe-EGCG to PCS. Specifically, in Example 3, the mass ratio of Fe-EGCG to PCS is 1:2.
[0074] The preparation steps for using the bio-based flame retardant composition of Example 3 to prepare polylactic acid composite material are the same as those in Example 1. The polylactic acid composite material sample of Example 3 is obtained by injection molding.
[0075] Example 4
[0076] The bio-based flame retardant composition of Example 4 is the same as that of Example 3. The only difference between Example 4 and Example 3 is the content of the bio-based flame retardant composition in the raw materials of the polylactic acid composite material. Specifically, the raw material ratio of the polylactic acid composite material of Example 4 is: 100 parts polylactic acid, 15 parts bio-based flame retardant composition, and 1 part diffusion oil.
[0077] The other preparation steps of Example 4 are the same as those of Example 3, and the polylactic acid composite material sample of Example 4 is obtained by injection molding.
[0078] Example 5
[0079] The bio-based flame retardant composition of Example 5 is the same as that of Example 3. The only difference between Example 5 and Example 3 is the content of the bio-based flame retardant composition in the raw materials of the polylactic acid composite material. Specifically, the raw material ratio of the polylactic acid composite material of Example 5 is: 100 parts polylactic acid, 20 parts bio-based flame retardant composition, and 1 part diffusion oil.
[0080] The other preparation steps of Example 5 are the same as those of Example 3, and the polylactic acid composite material sample of Example 5 is obtained by injection molding.
[0081] Comparative Example 1
[0082] The difference between Comparative Example 1 and Example 1 is that no bio-based flame retardant composition was added to the raw materials of the polylactic acid composite material. The other preparation steps were the same as those in Example 1, and the polylactic acid material sample of Comparative Example 1 was obtained by injection molding.
[0083] Comparative Example 2
[0084] The difference between Comparative Example 2 and Example 1 is that Fe-EGCG was not added to the bio-based flame retardant composition. The raw material ratio of the polylactic acid composite material of Comparative Example 2 is: 100 parts polylactic acid, 10 parts PCS, and 1 part diffusion oil (methyl silicone oil).
[0085] The other preparation steps of Comparative Example 2 were the same as those of Example 1, and the polylactic acid composite material sample of Comparative Example 2 was obtained by injection molding.
[0086] Comparative Example 3
[0087] The difference between Comparative Example 3 and Example 4 is that Fe-EGCG in the bio-based flame retardant composition was replaced with EGCG. Specifically, the bio-based flame retardant composition of Comparative Example 3 was prepared by mixing EGCG and PCS at a mass ratio of 1:2.
[0088] The other preparation steps of Comparative Example 3 were the same as those of Example 4, and the polylactic acid composite material sample of Comparative Example 3 was obtained by injection molding.
[0089] Comparative Example 4
[0090] The only difference between the bio-based flame retardant composition of Comparative Example 4 and the bio-based flame retardant composition of Example 1 is that the amount of P2O5 added in the raw materials for preparing PCS in step 1.2 is 3 parts, and all other conditions are the same. The degree of substitution of phosphate groups in the PCS prepared in Comparative Example 4 is 0.411.
[0091] When the bio-based flame retardant composition of Comparative Example 4 was used to prepare polylactic acid composite material, the raw material ratio of the polylactic acid composite material was: 100 parts polylactic acid, 15 parts bio-based flame retardant composition, and 1 part diffusion oil. The other preparation steps of the polylactic acid composite material of Comparative Example 4 were the same as those of Example 1, and the polylactic acid composite material sample of Comparative Example 4 was obtained by injection molding.
[0092] To further demonstrate the beneficial technical effects of the present invention, the mechanical properties, flame retardant properties, and thermal stability of the polylactic acid composite materials prepared in the specific embodiments and comparative examples of the present invention will be tested and compared below, including: mechanical property and flame retardant property testing, thermal stability testing, and scanning electron microscopy (SEM) testing.
[0093] 1. Mechanical properties and flame retardant properties testing
[0094] 1.1 Impact Strength Test
[0095] According to GB / T 1043.2-2018 standard "Determination of Impact Properties of Simply Supported Beams of Plastics - Part 2: Instrumented Impact Testing", the unnotched impact strength of polylactic acid composite material samples prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was tested. The test specimens were 80 mm long, 10 mm wide, and 4 mm thick. The pendulum energy of the impact testing machine was 4 J, and the support span was 58 mm. Ten valid specimens were tested in each group, and the average value of the test results was taken.
[0096] 1.2 Tensile strength test
[0097] According to GB / T 1040.2-2022 standard "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics", the tensile strength of polylactic acid composite samples prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was tested. The test specimens were standard dumbbell-shaped (Type 1A), with a total length of 170 mm, a thickness of 4 mm, an end width of 20 mm, a transition arc radius of 24 mm, and a narrow middle section measuring 80 mm in length, 10 mm in width, and 4 mm in thickness. During testing, the clamping length was 50 mm and axially aligned. The testing machine was started and stretched at a constant speed of 2 mm / min, and the stress-strain curve was recorded until the specimen fractured. Five valid specimens were tested in each group, and the average value of the test results was taken.
[0098] 1.3 Flame retardant performance test
[0099] According to UL 94, "Tests for Flammability of Plastic Materials for Parts in Device," the flame retardancy rating of polylactic acid composite samples prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were tested. The test specimens were rectangular strips measuring 127 mm in diameter, 12.7 mm in width, and 3 mm in thickness. Methane gas with a purity ≥ 99% was used, and a 50W Bunsen burner was adjusted to a flame height of 20 mm and a blue flame tip of 20 mm. The specimens were held vertically, with the distance between the Bunsen burner nozzle and the specimen being 120 mm. Five valid specimens were tested in each group, and the worst-performing specimen was used for rating.
[0100] The test results for unnotched impact strength, tensile strength, and flame retardancy rating are shown in Table 1.
[0101] Table 1 Test results of mechanical properties and flame retardant properties
[0102]
[0103] According to the test results in Table 1, compared with the comparative examples, Examples 1 to 5 of the present invention, which use bio-based flame-retardant compositions formed by compounding Fe-EGCG complexes with PCS to prepare polylactic acid composite materials, achieve excellent flame-retardant properties (UL-94 flame retardant rating of V-0 for all) while also exhibiting good impact strength and tensile strength. Specifically, compared with adding only PCS as a flame retardant (see Comparative Example 2), not only is the flame-retardant effect of the polylactic acid composite material improved, but the mechanical properties (impact strength and tensile strength) of the polylactic acid material are also improved. Compared with Comparative Example 1 without added flame retardant, Examples 1 to 5 of the present invention effectively control the decrease in tensile strength while improving impact strength and flame retardancy, and the decrease in tensile strength is smaller than that of adding only PCS as a flame retardant (Comparative Example 2). In addition, compared with the flame-retardant effect (V-1 rating) of Comparative Example 4, which has a reduced degree of substitution of phosphate groups in PCS, the flame-retardant effect of Examples 1 to 5, which use PCS with a degree of substitution of phosphate groups greater than 0.5, is significantly improved.
[0104] 2. Thermal stability test
[0105] Thermogravimetric analysis (TGA) was performed on the polylactic acid composite material sample prepared in Example 3 and the polylactic acid sample in Comparative Example 1. Test conditions: air as the test atmosphere, heating rate of 10℃ / min, and test temperature range of 30~800℃. Test results are as follows: Figure 3 As shown.
[0106] The thermal stability test results show that the polylactic acid composite material prepared in Example 3 has comparable thermal stability to that prepared in Comparative Example 1, indicating that the bio-based flame retardant composition prepared by compounding M-EGCG complex and PCS does not reduce the thermal stability of polylactic acid.
[0107] 3. Scanning electron microscopy (SEM) observation
[0108] The fracture surfaces of the polylactic acid composite materials prepared in Example 1 and Comparative Example 2 after impact strength testing were observed using scanning electron microscopy. The observed microstructures are as follows: Figure 4 As shown, region (a) corresponds to the polylactic acid composite material prepared in Comparative Example 2 (without Fe-EGCG), and region (b) corresponds to the polylactic acid composite material prepared in Example 1. Comparison of the fracture surface microstructures of Example 1 and Comparative Example 2 reveals that the fracture surface of Example 1 is smoother and flatter, without fine voids or delamination, indicating that the addition of Fe-EGCG improves the interfacial bonding between PCS and PLA.
[0109] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the term "comprising" does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0110] The above embodiments are only used to illustrate the technical solutions of the present invention and should not be used to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments or equivalent substitutions can be made to some of the technical features without departing from the essence and scope of the present invention. Such modifications or equivalent substitutions still fall within the scope of the present invention.
Claims
1. The application of a bio-based flame retardant composition in the preparation of polylactic acid composite materials, wherein the bio-based flame retardant composition comprises: Phosphorylated chitosan, with a viscosity greater than 400 mPa·s and a degree of substitution of phosphate groups Ds not less than 0.5; M-EGCG, where M is a transition metal element, and M-EGCG is a complex of epigallocatechin gallate ester EGCG and a transition metal ion; The mass ratio of M-EGCG to phosphorylated chitosan is 1:1~5.
2. The application as described in claim 1, wherein, The mass ratio of M-EGCG to phosphorylated chitosan is 1:2~4.
3. The application as described in claim 1 or 2, wherein, M is selected from one of the following elements: Fe, Cu, Zn, Ni.
4. The application as described in claim 1, wherein, The phosphorylated chitosan is formed by the phosphorylation reaction of chitosan, and the viscosity of the chitosan is in the range of 200~800 mPa.s, with a degree of deacetylation ≥80%.
5. The application as described in claim 1, wherein, The M-EGCG is Fe-EGCG.
6. The application as described in claim 1, wherein, M-EGCG is formed by the reaction of EGCG with transition metal halides.
7. A method for preparing a polylactic acid composite material, characterized in that, The bio-based flame retardant composition as described in claim 1 is added to the raw materials used in the preparation, the bio-based flame retardant composition comprising: Phosphorylated chitosan, with a viscosity greater than 400 mPa·s and a degree of substitution of phosphate groups Ds not less than 0.5; M-EGCG, where M is a transition metal element, and M-EGCG is a complex of epigallocatechin gallate ester EGCG and a transition metal ion; The mass ratio of M-EGCG to phosphorylated chitosan is 1:1~5.
8. The preparation method according to claim 7, wherein, The mass ratio of M-EGCG to phosphorylated chitosan is 1:2~4.
9. The preparation method according to claim 7, wherein, M is selected from one of the following elements: Fe, Cu, Zn, Ni.
10. The preparation method according to claim 7, wherein, The phosphorylated chitosan is formed by the phosphorylation reaction of chitosan, and the viscosity of the chitosan is in the range of 200~800 mPa.s, with a degree of deacetylation ≥80%.
11. The preparation method according to claim 7, wherein, The M-EGCG is Fe-EGCG.
12. The preparation method according to claim 7, wherein, M-EGCG is formed by the reaction of EGCG with transition metal halides.
13. The preparation method according to claim 7, wherein, The raw material composition of the polylactic acid composite material, calculated by parts by weight, is as follows: 100 parts of polylactic acid; 5-25 parts of bio-based flame retardant composition.
14. The preparation method according to claim 13, wherein, The bio-based flame retardant composition is 10-20 parts.
Citation Information
Patent Citations
EGCG / Zn-CS and preparation method and application thereof
CN117964792A